Pemanfaatan Tepung Biji Nangka dalam Pembuatan Mi Kering Utilization Of Jackfruit Seed Flour In The Manufacture Of Dry Noodles - Indra Wijaya; Netti Herawati; Usman Pato (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
Dried noodles are food products made from wheat flour with the addition of other foodstuffs and permitted food additions and typical form of noodles.  Dry noodles in this study were made from jackfruit seed flour and wheat flour with the addition of ingredients of soy protein isolates and pumpkin puree. The purpose of this study was to get the best ratio of jackfruit seed flour in the manufacture of dried noodles that meet SNI 8217-2015 dry noodles.  Treatment in the study was the difference in ratio between jackfruit and wheat flour, namely TN1 (90:10), TN2 (80:20), TN3 (70:30) and TN4 (60:40).  The study used a complete randomized design (CRD) with four treatments and four repeats.  The data obtained was then statistically analyzed using analysis of variance (ANOVA) and followed by Duncan's Multiple Range Test (DMRT) at 5%.  The results showed that the use of jackfruit seed flour in chemical analysis had a real effect on chemical parameters in this study except on fat content parameters, while in organoleptic assessment had a real effect except on color parameters and density hedonically.  TN1 treatment with wheat flour and jackfruit seed flour ratio (90:10) was chosen as the best treatment that has chemical characteristics of moisture content 8.21%, ash 4.49%, protein 15.67%, fat 0.1%, carbohydrate 71.52%, coarse fiber 0.73%, wholeness of noodles 98.62% and rehydration time of 5.5 minutes as well as a descriptive color score of 3.4 (somewhat yellow-brown), aroma score of 2.53 (somewhat flavorful of jackfruit seeds), fragility score of 3.07 (somewhat hard) and hedonic color score of 4.30 (likes), aroma score of 3.57 (likes), fragility score of 3.73 (likes), overall rating score of 3.93 (likes). Keyword: Dried noodles, wheat flour, jackfruit seed flour